2021
DOI: 10.1097/ijg.0000000000001823
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical Outcomes After XEN Gel Stent and EX-PRESS Glaucoma Drainage Device Implantation

Abstract: Precis: Although the XEN stent offers a lower risk of hypotony and choroidal effusions with fewer clinic visits postoperatively, its surgical success rate was inferior to the EX-PRESS shunt.Purpose: To compare the clinical efficacy and safety outcomes of the XEN stent and EX-PRESS glaucoma drainage device in glaucomatous eyes.Materials and Methods: One hundred eyes from 88 patients underwent ab interno XEN stent or EX-PRESS shunt implantation (52 XEN and 48 EX-PRESS) for uncontrolled glaucoma at the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…However, some studies focused on the efficacy of XEN implantation in the treatment of secondary openangle glaucoma, including pseudoexfoliative glaucoma (52,60,(67)(68)(69)(70) and glaucoma secondary to uveitis (34). Furthermore, a few studies introduced this gel stent to narrow-or closeangle glaucoma (13,15,16,(18)(19)(20)(21)50). All patients were treated and followed as routine clinical practice between May 2013 and February 2020.…”
Section: Overall Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, some studies focused on the efficacy of XEN implantation in the treatment of secondary openangle glaucoma, including pseudoexfoliative glaucoma (52,60,(67)(68)(69)(70) and glaucoma secondary to uveitis (34). Furthermore, a few studies introduced this gel stent to narrow-or closeangle glaucoma (13,15,16,(18)(19)(20)(21)50). All patients were treated and followed as routine clinical practice between May 2013 and February 2020.…”
Section: Overall Resultsmentioning
confidence: 99%
“…Cases of stent malposition needed to remove or reimplant of the stent (12). Bleb-related complications comprised bleb leakage (0.68%) and dysesthetic blebs (0.01%) that required sutures (34,53) or revisions (15,35,75).…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Xen vs. EX were 15.6% vs. 55.6% and 17.8% vs. 55.6%, respectively. Therefore, they concluded that Xen was inferior to EX for complete success [ 29 ]. Further studies are needed to determine whether all filtering surgeries using MMC for controlling IOP via laser suture lysis through a scleral flap are superior to single insertion Xen and Preserflo.…”
Section: Discussionmentioning
confidence: 99%